2013
DOI: 10.1177/0218492313506921
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of surgical management of type A aortic dissection

Abstract: Our results identify the major risk factors for perioperative and long-term mortality. Age is an independent risk factor for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…No significant differences in the 5-year survival between the groups were observed. Similar results were obtained by Skripochnik et al [ 22 ]; in assessing 1- and 4-year survival, they noted no significant differences between patients in the mini-invasive and those in full access groups. However, Merk et al reported higher 5- and 8-year survival rates in patients who underwent minimal access operation than in those who underwent traditional interventions [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…No significant differences in the 5-year survival between the groups were observed. Similar results were obtained by Skripochnik et al [ 22 ]; in assessing 1- and 4-year survival, they noted no significant differences between patients in the mini-invasive and those in full access groups. However, Merk et al reported higher 5- and 8-year survival rates in patients who underwent minimal access operation than in those who underwent traditional interventions [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…Contemporary reports showed 10% to 25% perioperative mortality in spite of advances in techniques and perioperative management (3)(4)(5)12). These numbers increase dramatically when there is hemodynamic compromise at presentation (1,2,(5)(6)11,13,14). Hence, early recognition and surgical correction is recommended to prevent aortic rupture, repair the aortic regurgitation, and restore flow to end-organs (2,14).…”
Section: Discussionmentioning
confidence: 99%
“…Axillary artery cannulation has the advantage of delivering cerebral perfusion through the initial cannulation site. There is less risk for visceral malperfusion, but it can be technically demanding in large patients, requires a separate incision, has been associated with brachial plexus injury and arm ischemia, and can cause insufficient systemic CPB flow if the vessel is small, has a serpentine course, atherosclerotic, or is itself dissected (9,13,23,24). Innominate artery cannulation, first described by Banbury and Cosgrove in 2000, is less commonly used (23).…”
Section: Cannulation Techniquementioning
confidence: 99%
“…Most series addressing surgery for acute type A aortic dissection focus on perioperative outcome and often lack reporting of survival greater than 4 years. 3,[6][7][8][9][10] The few contemporary trials with longer follow-up show comparable outcomes. 11 However, patient number reported is substantially smaller in most studies.…”
Section: Discussionmentioning
confidence: 99%